PENGARUH DOSIS PUPUK KCL TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA KULTIVAR PADI GOGO LOKAL ACEH TIMUR - Raibah, Erza Didah; S, Risyad; S, Bahri (Agrobun, 2025)
· Introduction: Efforts are needed to increase rice production through innovative technological breakthroughs. These breakthrough efforts must utilize a more practical approach with balanced intensification between increasing productivity and conserving resources. Therefore, it is necessary to research the optimum dosage of KCl fertilizer for local upland rice in East Aceh· Materials and Methods: This research was conducted at the experimental field of the Faculty of Agriculture, Samudra University, Langsa City, Aceh Province, with an altitude of ± 10 meters above sea level and soil pH of 5.9. The research was arranged using a factorial randomized complete block design (RCBD), consisting of two factors: 5 levels of KCl fertilizer dosage and 5 levels of local upland rice cultivars from Aceh. Parameters observed included plant height, number of tillers, number of productive tillers, days to flowering, days to maturity, yield per plant, and yield per plot.· Results: The results showed that the dosage of KCl fertilizer significantly affected plant height, number of tillers, number of productive tillers, days to flowering, days to maturity, yield per plant, and yield per plot. However, it did not significantly affect plant height and number of tillers. The research also indicated that the local upland rice cultivars from East Aceh significantly affected plant height, number of tillers, and number of productive tillers. The interaction between KCl fertilizer dosage and local upland rice cultivars from East Aceh significantly affected the number of tillers per hill and significantly affected plant height, number of tillers, yield per plant, and yield per plot. However, it did not significantly affect plant height in some growth stages.